Knockdown of Nrf2 suppresses glioblastoma angiogenesis by inhibiting hypoxia‐induced activation of HIF‐1α. Issue 3 (10th January 2014) - Ji, Xiangjun; Wang, Handong; Zhu, Jianhong; Zhu, Lin; Pan, Hao; Li, Wei; Zhou, Yuan; Cong, Zixiang; Yan, Feng; Chen, Suihua
<x xml:space="preserve">Abstract</x> Concerns were increasingly raised that several types of cancers overexpressed the nuclear factor erythroid 2‐related factor 2 (Nrf2), which contributed strikingly to cancer biological capabilities and chemoresistance. However, the role of Nrf2 in the tumor vascular biology had yet to be mechanistically determined. Here, we investigated the involvement of Nrf2 in glioblastoma (GB) angiogenesis in hypoxia. First, we detected the overexpression of Nrf2 and correlated its protein level with microvessel density (MVD) in human GB tissues. Then, we established the stable RNAi‐mediated Nrf2‐knockdown cells and mimicked hypoxic condition in vitro. The knockdown of Nrf2 inhibited cell proliferation in vitro and suppressed tumor growth in mouse xenografts with a concomitant reduction in VEGF expression and MVD. Similar antiangiogenic effects were documented in endothelial tube formation assays. The downregulation of Nrf2 in glioma cells led to much lower accumulation of HIF‐1α protein and limited expression of VEGF and other HIF‐1α target genes in mimicking hypoxia. Mechanistic investigations suggested that HIF‐1α degradation during hypoxia could be attributed to reduced mitochondrial O2 consumption in Nrf2‐inhibited cells. It can be concluded that Nrf2, with its capacity for affecting the protein level of HIF‐1α expression, has good reasons to be considered as a critical transcription factor for controlling glioma angiogenesis.